Peningkatan Hasil Belajar Mengoperasikan Sistem Pengendali Programmable Logic Controller (PLC) Menggunakan Media Pembelajaran Trainer pada Siswa Kelas XII di SMKN 4 Kota Serang Tahun Pelajaran 2021/2022 - Gunawan , Rohmat (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2022)
This study aims to determine the results of learning to operate the Programmable Logic Controller (PLC) control system using trainer learning media in class XII students at SMKN 4 Kota Serang. This study uses the Action research method, starting from: a) planning, b) action and observation, c) reflection. The research process was carried out into two cycles. The subjects in this study were students of class XII TL, Department of Electrical Installation Engineering at SMKN 4 Kota Serang who were involved in the learning process of Electric Motor Installation, totaling 35 people. Using the observation research method, the type of observation used is open observation. Data analysis techniques was using qualitative data analysis. The results show an increase, in the first cycle the percentage of passing was 52.5%. These learning outcomes increased in cycle II where 35 students had received KKM passing grades so that completeness reached 87.5%.